2021
DOI: 10.1021/acsami.1c00690
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Selenium Quantum Dots for the Treatment of Alzheimer’s Disease by Reducing Aβ-Neurotoxicity and Oxidative Stress and Alleviate Neuroinflammation

Abstract: At present, the complex pathogenesis, the difficult-to-overcome blood–brain barrier (BBB), the development of the disease course which cannot be prevented, and other problems are serious challenges in the treatment of Alzheimer’s disease (AD). In order to enhance the therapeutic effect of drugs through BBB, we synthesized simple and easy-to-obtain selenium quantum dots (SeQDs), with a multitarget therapeutic effect. This new type of SeQDs has an ultrasmall size and can quickly penetrate the BBB. According to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 51 publications
(69 reference statements)
0
45
0
Order By: Relevance
“…In recent decades, the role of nanoparticles in neurological diseases has been actively studied, since neurons are especially vulnerable to damage caused by oxidative stress due to high oxygen consumption, the presence of a large amount of polyunsaturated fatty acids, and a low level of expression of antioxidant enzymes [ 37 , 38 ]. The other types of brain-resident cells such as microglia and vascular endothelial cells are also targets for the treatment of neurodegeneration with selenium nanoparticles and selenium quantum dots [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, the role of nanoparticles in neurological diseases has been actively studied, since neurons are especially vulnerable to damage caused by oxidative stress due to high oxygen consumption, the presence of a large amount of polyunsaturated fatty acids, and a low level of expression of antioxidant enzymes [ 37 , 38 ]. The other types of brain-resident cells such as microglia and vascular endothelial cells are also targets for the treatment of neurodegeneration with selenium nanoparticles and selenium quantum dots [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced concentration of selenium as an antioxidant could be associated with AD because of oxidative stress induced by other metals/metalloids (chromium, arsenic, etc.). Experimental studies show a decisive role of selenium in AD pathogenesis via abilities to reduce mitochondrial oxidative stress [ 60 ], to inhibit metal-induced Aβ aggregation [ 33 ] and to reduce Tau hyperphosphorylation [ 61 , 62 ]. Meanwhile, the findings of epidemiological studies are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced expression of the pro-inflammatory cytokines induced by CdSe-QDs falls in line with the findings of Tosic and co-workers [30], who noted that graphene-QDs suppress experimental autoimmune encephalomyelitis in rats by reducing spinal cord demyelination and axonal damage, and T-helper 1 development and spinal cord inflammation, and by blocking (in vitro) T-cell-induced oligodendrocyte/neuron damage. A recent study reports that Se-QDs are able to alleviate neuroinflammation and to improve memory impairment, learning and memory ability in a mouse model of Alzheimer's disease [31]. Overall, more studies are needed to determine whether the reported alterations to immune and inflammatory pathways and processes are able to induce the adverse typically described effects or, conversely, can offer the potential beneficial effects described by Tosic et al [30] and by Guo et al [31].…”
Section: Inflammation and Immune System Alterationsmentioning
confidence: 99%
“…A recent study reports that Se-QDs are able to alleviate neuroinflammation and to improve memory impairment, learning and memory ability in a mouse model of Alzheimer's disease [31]. Overall, more studies are needed to determine whether the reported alterations to immune and inflammatory pathways and processes are able to induce the adverse typically described effects or, conversely, can offer the potential beneficial effects described by Tosic et al [30] and by Guo et al [31].…”
Section: Inflammation and Immune System Alterationsmentioning
confidence: 99%